2021
DOI: 10.31181/rme200102031m
|View full text |Cite
|
Sign up to set email alerts
|

Dual solutions for MHD flow of a water-based TiO2-Cu hybrid nanofluid over a continuously moving thin needle in presence of thermal radiation

Abstract: In this analysis, the flow and heat transfer characteristics of an aqueous hybrid nanofluid with TiO2 and Cu as the nanoparticles past a horizontal slim needle in the presence of thermal radiation effect is investigated. We hope that the present research is applicable in fiber technology, polymer ejection, blood flow, etc. The Prandtl number of the base fluid is kept constant at 6.2. The needle is considered thin when its thickness does not exceed that of the boundary layer over it. Using the similarity transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Effective thermophysical models of the hybrid nanofluid 5,12,14,23,25 An important note in Figure 2 is that we used the Esfahani et al 23 model for effective thermal conductivity which is only valid for the ZnO-Ag/water hybrid nanofluid. It is a function of volume fraction and temperature and we assumed here that the temperature is kept constant at 298 K. Furthermore, Figure 3 briefly presents the mass-based algorithm for the hybrid nanofluids.…”
Section: Off-centered Stagnation Point Flow: Problem Schematic and Fo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Effective thermophysical models of the hybrid nanofluid 5,12,14,23,25 An important note in Figure 2 is that we used the Esfahani et al 23 model for effective thermal conductivity which is only valid for the ZnO-Ag/water hybrid nanofluid. It is a function of volume fraction and temperature and we assumed here that the temperature is kept constant at 298 K. Furthermore, Figure 3 briefly presents the mass-based algorithm for the hybrid nanofluids.…”
Section: Off-centered Stagnation Point Flow: Problem Schematic and Fo...mentioning
confidence: 99%
“…Effective thermophysical models of the hybrid nanofluid 5,12,14,23,25 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Off‐centered Stagnation Point Flow: Problem Schematic and Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dolon et al [47] studied the flow analyses as well as the centrifugal influence in the duct size. Mousavi et al [48] conducted nanofluid and thermal radiation through a needle to narrate the velocity ratio for the change of magnetic parameters. Bibin et al [49] used vector plot to represent the axial velocity and showed temperature contour at several axial locations.…”
Section: Validation Of the Studymentioning
confidence: 99%
“…As a result, researchers incorporated thermal radiation in their research work. Mousavi et al [35] focused his research to examine the significance of thermal radiation over the MHD flow of TiO 2 − Cu∕water hybrid nanoliquid toward the thin needle with dual solution and applied the bvp4c technique in MATLAB for their graphical discussion. Haider et al [36] debated the occurrence of thermally radiated activation energy on the unsteady magnetohydrodynamic flow of fluid under the stretched surface.…”
Section: Introductionmentioning
confidence: 99%